Somatosensory evoked potentials in patients with obstructive sleep apnea syndrome and cerebral hypoxia (Annals of Medical Research, 2021)
None
Keywords: Keypoint electromyography device (Version 2.38, Medtronic Dantec, Skovlunde, Denmark) in patients, diagnosed with severe OSAS as compared to control group in polysomnography lab of Department of Chest Diseases. Potential cortical (N20) latency and amplitudes were compared between patients and control group.br /Results: Even if the average of SEP N20 latency was within the normal limits in patients group, (diagnosed with severe OSAS according to clinical and polysomnography examination), it was clearly extended and statistically significant compared to control group. (Respectively 22.31±2.13 ms, 18.35±0.80 ms P= 0.000). Moreover, when the amplitudes of obtained N20 potentials were compared between patients and control group, it was determined that the amplitudes of patients group were clearly lower and statistically significant. (Respectively 1.82±0.16 mv, 2.54±0.25 mv, P=0.000). The average of Apnea-Hypopnea index (AHI) was detected as 55.77±28.02. However, there was no correlation detected between AHI and SEP (p=0.164, r=0.261).br /Conclusion: These results indicate the existence of cerebral hypoxia in OSAS and at the same time highlight the importance of SEP examinations in OSAS.br / Obstructive Sleep Apnea Syndrome; Somatosensory Evoked Potential; Cerebral Hypoxia.